Electrochromic Device Composed of a Di-Urethanesil Electrolyte Incorporating Lithium Triflate and 1-Butyl-3-Methylimidazolium Chloride - Gonçalves, Maria Cristina (2021)
UID/QUI/00686/2016 UID/QUI/00686/2018 UID/QUI/00686/2019 PEst-OE/QUI/UI0616/2016 FCOMP-01-0124-FEDER037271 POCI01-0145-FEDER-016884 PTDC/CTM-NAN/0956/2014 SAICTPAC/0032/2015 POCI-01-0145FEDER-016422 POCI-010145-FEDER-030858 PTDC/BTM-MAT/30858/2017